Twice-Exceptional Students: Review of Implications for Special and Inclusive Education - Marcin Gierczyk; Garry Hornby (MDPI AG, 2021)
The purpose of this article is to review recent literature on twice-exceptional students and consider implications for their education in the context of the trend towards increased inclusive education for students with disabilities. The review focused on teachers' experiences and perceptions and the school experiences of twice-exceptional students. Fifteen articles were reviewed, published between 2000 and 2020, selected according to a systematic protocol from two widely used online databases. Findings indicated that the implications that need to be considered were the importance of teacher preparation, the need for a continuum of special education interventions, the need for collaboration with parents and specialists, and teachers needing to focus on developing strengths as much as remediating difficulties. It was concluded that twice-exceptional students can be taught effectively in inclusive education settings as long as they are able to access appropriate strategies and programs from the fields of special education and gifted education.